1997
DOI: 10.1074/jbc.272.41.25547
|View full text |Cite
|
Sign up to set email alerts
|

Low Barrier Hydrogen Bond Is Absent in the Catalytic Triads in the Ground State but Is Present in a Transition-state Complex in the Prolyl Oligopeptidase Family of Serine Proteases

Abstract: High frequency proton NMR spectra for two members of the prolyl oligopeptidase class of serine proteases, prolyl oligopeptidase and oligopeptidase B, showed that resonances corresponding to the active center histidine Ndelta1H and Nepsilon2H generally observed in this region, are absent in these enzymes. However, for both enzymes, as well as with the H652A and H652Q active center variants of oligopeptidase B, there are two resonances observed in this region that could be assigned to two protonated histidines w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…We found the same resonance in all of our mutant proteins, free and complexed with either inhibitor, suggesting that this signal does not arise from an active-site residue. A similar observation has been reported for serine proteases belonging to the class of prolyl oligopeptidases: prolyl oligopeptidase (PO) and oligopeptidase B of Escherichia coli (OpB) (Kahayaoglu et al 1997). Downfield chemical shifts (;17 and ;16 ppm) were observed for the wild type and an active-site H652A mutant of OpB.…”
Section: Y547fsupporting
confidence: 55%
“…We found the same resonance in all of our mutant proteins, free and complexed with either inhibitor, suggesting that this signal does not arise from an active-site residue. A similar observation has been reported for serine proteases belonging to the class of prolyl oligopeptidases: prolyl oligopeptidase (PO) and oligopeptidase B of Escherichia coli (OpB) (Kahayaoglu et al 1997). Downfield chemical shifts (;17 and ;16 ppm) were observed for the wild type and an active-site H652A mutant of OpB.…”
Section: Y547fsupporting
confidence: 55%
“…24,25,32,33 Even among serine proteases, it has been reported that the prolyl oligopeptidase family exhibits important dissimilarities in the active site compared to the pancreatic and subtilisin classes of serine proteases. 34 In the case of the prolyl oligopeptidase, non-catalytic histidine imidazole ring-attached protons are engaged in relatively strong hydrogen bonds based on the observation that their downfield chemical shifts are virtually independent of pH up to pH 9.5. 34 Furthermore, while in most situations a LBHB involves a carboxyl group from Asp and Glu residues, 35 our results indicate that this is not always the case.…”
Section: Discussionmentioning
confidence: 99%
“…34 In the case of the prolyl oligopeptidase, non-catalytic histidine imidazole ring-attached protons are engaged in relatively strong hydrogen bonds based on the observation that their downfield chemical shifts are virtually independent of pH up to pH 9.5. 34 Furthermore, while in most situations a LBHB involves a carboxyl group from Asp and Glu residues, 35 our results indicate that this is not always the case. Conclusive assignment of the downfield proton resonance, to the specific His residue as well as to the specific ring nitrogen in our case, is important for the interpretation of experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary analysis of OpdB function in the context of bacterial growth and protein turnover has been undertaken with Salmonella (13). A preliminary kinetic characterization of the E. coli enzyme illustrated that it cleaved substrates at the C terminus of basic residues, exhibited pronounced substrate inhibition and that the enzyme-substrate interaction was disrupted by high ionic strength, implicating ionic interactions in substrate binding (16,29,32). However, OpdB homologues from prokaryotes have not been extensively characterized, particularly with respect to substrate recognition properties and roles in bacterial virulence.…”
mentioning
confidence: 99%